Diversification of Local Food Products through Banana Heart Processing - Nurliani; Suherah; Agustrai; Mukhlis (Pascasarjana Universitas Mataram, 2025)
The demand for animal protein is increasing in line with public awareness of the importance of balanced nutrition, population growth, and increased purchasing power. Satay and shredded meat are popular foods that are sources of animal protein. The price of meat continues to rise, prompting people to seek alternative products that are less expensive to produce yet still nutritious. Processing banana hearts into banana heart satay can be an alternative solution. The